The Timber Value of an Existing Forest Stand - Andres Susaeta (EDIS)
This 4-page publication presents a straightforward and intuitive approach based on compounding costs to determine the timber value of a forest at any stage of its development. Written by Andres Susaeta, and published by the UF/IFAS School of Forest, Fisheries, and Geomatics Sciences, March 2021.